DAMPAK PROGRAM BANTUAN LANGSUNG TUNAI TERHADAP PEREKONOMIAN DAN UMKM DI DESA KARANG REJO KABUPATEN SIMALUNGUN SUMATERA UTARA - Nurkhaliza Novianty; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
The Covid pandemic has had a huge economic impact. The enactment of the PSBB and PPKM rules to stop the chain of transmission of Covid 19 actually had a big impact on people's lives, especially the economic aspect. This research focuses on analyzing the impact of the Covid 19 Direct Cash Assistance during the past pandemic. The purpose of this research is to find out in detail how the cash advance assistance program mechanism works for the community and MSMEs and what impact it has. The aim of this program is to help people's lives in dealing with difficult pandemic situations. Especially in meeting daily needs. The method used in this study is qualitative accompanied by field observations. This study used a qualitative method, conducted by interviewing Nagori Officials, as well as the Community who received Direct Cash Assistance. From the results of the research, it was found that the Covid 19 BLT policy in Nagori Karang Rejo, Mount Maligas, Simalungun Regency, was very beneficial for the community, and had a positive impact on the people's economy. However, there are obstacles faced, namely the lack of proper targeting of the distribution of aid, and also the limited aid funds. While BPUM assistance for MSMEs has problems, BPUM recipients are only for those who have officially registered their business. While those with informal status are still difficult to get help. Keywords: Covid 19 Direct Cash Assistance, BPUM Assistance, Impact of Assistance on the economy of Nagori Karang Rejo. Obstacles